Respiratory function and cognitive profile in amyotrophic lateral sclerosis. (11th December 2019) - Huynh, W.; Sharplin, L. E.; Caga, J.; Highton‐Williamson, E.; Kiernan, M. C.
Abstract : Background and purpose: Amyotrophic lateral sclerosis (ALS) is increasingly recognized as a multisystem disorder with 30%–50% of patients exhibiting cognitive impairment. The pathophysiological mechanisms of cognitive dysfunction are probably multifactorial although hypoventilation secondary to respiratory dysfunction may contribute to cognitive decline. The current study aimed to identify the relationship between respiratory function in ALS patients and the presence and degree of cognitive impairment. Methods: Amyotrophic lateral sclerosis patients were prospectively recruited from a multidisciplinary ALS clinic. Baseline clinical assessments including respiratory function as assessed by spirometry were recorded with forced vital capacity (FVC) ≤ 75% considered to be reduced respiratory function. Cognitive testing was performed utilizing the Addenbrooke's Cognitive Examination (ACE) and the Mini‐Mental State Examination (MMSE). Results: From a cohort of 100 ALS patients, 48% were categorized as having impaired respiratory function (FVC = 58.24% ± 2.15%) whilst 52% had normal function (88.65% ± 1.27%). Compared to the group with normal respiratory function (ACE 90.68 ± 0.89, MMSE 28.22 ± 0.21), patients with respiratory dysfunction had significantly reduced cognitive function (ACE 86.83 ± 1.5, P = 0.025; MMSE 26.29 ± 0.45, P = 0.029). Furthermore, subscores demonstrated significant differences between the groups with respect to domains in memory ( P = 0.003) and attention ( P = 0.05) with a trend observed in fluency ( P = 0.082). There was a significant correlation between patient baseline FVC and ACE scores as well as between FVC and memory and fluency subscores ( P < 0.01). Conclusion: Amyotrophic lateral sclerosis patients with respiratory compromise were more likely to develop reduced cognitive function. In addition to improving physical function, it remains plausible that non‐invasive ventilation may alter the progression of cognitive impairment in ALS patients and potentially improve overall quality of life and carer burden.